Analisis Pengaruh Assurance, Menu, External Environment, Accuracy, Food Quality, Responsiveness, Hygiene Quality, Interior Design, Atmosphere, Price terhadap Customer Loyalty Melalui Customer Satisfaction pada Kafe X Sidoarjo - Jessica Juventia; Ronald Suryaputra; Amelia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Population growth is in line with the growth of the economy in Sidoarjo City. In 2022, Sidoarjo City will increase its economy by 7 percent. This is influenced by several factors, one of which is the large number of MSMEs emerging in Sidoarjo. One of the MSMEs that has emerged is in the food and beverage industry, namely The Rooster Coffee and Company Sidoarjo which has a vintage design and was founded in 2018. The purpose of this research is to determine the influence of Assurance, Menu, External Environment, Accuracy, Food Quality, Responsiveness, Hygiene Quality, Interior Design Atmosphere, and Price on Customer Loyalty through Customer Satisfaction of customers of The Rooster Coffee and Company in Sidoarjo. The benefit of this research is to provide information, knowledge and broaden insight in the field of management regarding the variables used in this research. Using snowball sampling, 200 respondents in Sidoarjo were collected and processed with the help of AMOS version 22.0 software using the Structural Equation Model (SEM). The research results show that the variables Assurance, External Environment, Accuracy, Food Quality, Responsiveness, Hygiene Quality, Atmosphere, and Price significantly and positively influence Customer Satisfaction, except for the Menu and Interior Design variables which do not significantly influence Customer Satisfaction. The research results further show that Customer Satisfaction has a significant positive influence on Customer Loyalty.